Steroid therapy for COVID-19: A systematic review and meta-analysis of randomized controlled trials - Boppana, Tarun Krishna; Mittal, Saurabh; Madan, Karan; Mohan, Anant; Hadda, Vijay; Tiwari, Pawan; Guleria, Randeep (Monaldi Archives for Chest Disease, 2021)
There is an urgent need for effective treatment modalities for coronavirus disease 2019 (COVID-19). Data for the use of steroids in COVID-19 is emerging. We conducted this systematic review and meta-analysis to estimate the effectiveness of steroid administration in mortality reduction due to COVID-19 compared to the control group. A systematic search of the Pubmed and Embase databases was performed to extract randomized controlled trials (RCTs) regarding the use of steroid therapy for COVID-19. An overall and subgroup (based upon the type of steroid) pooled mortality analysis was performed, and odds ratios were reported. Cochrane risk of bias assessment tool was used to assess the risk of bias. Heterogeneity was assessed using the I2 statistic. Six RCTs, including 7707 patients, were selected for review. Three trials reported 28-day mortality, and two trials reported 21-day mortality, and one trial reported in-hospital mortality. There were 730 deaths among 2837 participants in the steroid group while 1342 deaths among 4870 patients randomized to the control group (Odds ratio 0.76, 95% confidence interval 0.58-1.00, p=0.05). The effect was significant in patients on oxygen or mechanical ventilation. There was no difference in the various preparations and doses of the steroids. There was heterogeneity among the trials as the I2 value was 53%, with a p-value of 0.06. There was no indication of increased serious adverse events. This meta-analysis of RCTs demonstrated that the use of systemic corticosteroids is associated with a reduction in all-cause mortality in patients with COVID-19 on oxygen or mechanical ventilation.